Integrating Socially Responsible Computing Competencies in Computer Science and Software Engineering Education - Olga Petrovska (Proceedings of the 9th Conference on Computing Education Practice, 2025)
We aim to explore and develop strategies for incorporating socially responsible computing into the foundational curriculum of computer science and software engineering programs in higher education in the UK. The objectives of the collaborative session are: reviewing the components of socially responsible computing - ethics, sustainability, societal impact and equity, governance and data protection, security; identifying essential competencies that should be fostered from early on in the program; developing actionable learning outcomes and curriculum changes to embed these principles from the outset.